Effect of the filtration with bleaching earths on several quality parameters of the biodiesel obtained from african palm oil - Albis- Arrieta, Alberto- Ricardo; Barros- Mendoza, Carlos- Alberto; Cabarcas- Núñez, Oscar- Eliecer (CT&F - Ciencia, Tecnología y Futuro, 2017)
In this work, we studied the performance of bleaching earths as removal agents of Total Contamination from samples of Colombian biodiesel obtained from palm oil. The effect of temperature and the dose of three commercial adsorbents were studied on quality parameters, Total Contamination and moisture of biodiesel. Results showed a complex behavior of the study variables on Total Contamination and final moisture; but either almost or no effects on other quality parameters such as free glycerin, total glycerin and pour point. Response surfaces showed that the values of the manipulated variables that improved the removal of Total Contamination in biodiesel also increased final moisture in the samples. Therefore, it was necessary to compute optimum values using desirability functions, which gave values for Total Contamination and final moisture, of 5.5 mg/kg and 562 mg/kg, respectively, using 0.48% of Bleaching Earth BE1 at 30°C.